Use of a new vertical traction device for early traction-assisted staged closure of congenital abdominal wall defects: a prospective series of 16 patients - Ziegler, Anna-Maria; Svoboda, Daniel; Lüken-Darius, Britta; Heydweiller, Andreas; Kahl, Fritz; Falk, Sophie Christine; Rolle, Udo; Theilen, Till-Martin (Pediatric surgery international, 2024)
Purpose: Abdominal wall closure in patients with giant omphalocele (GOC) and complicated gastroschisis (GS) remains to be a surgical challenge. To facilitate an early complete abdominal wall closure, we investigated the combination of a staged closure technique with continuous traction to the abdominal wall using a newly designed vertical traction device for newborns. Methods: Four tertiary pediatric surgery departments participated in the study between 04/2022 and 11/2023. In case primary organ reduction and abdominal wall closure were not amenable, patients underwent a traction-assisted abdominal wall closure applying fasciotens®Pediatric. Outcome parameters were time to closure, surgical complications, infections, and hernia formation. Results: Ten patients with GOC and 6 patients with GS were included. Complete fascial closure was achieved after a median time of 7 days (range 4–22) in GOC and 5 days (range 4–11) in GS. There were two cases of tear-outs of traction sutures and one skin suture line dehiscence after fascial closure. No surgical site infection or signs of abdominal compartment syndrome were seen. No ventral or umbilical hernia occurred after a median follow-up of 12 months (range 4–22). Conclusion: Traction-assisted staged closure using fasciotens®Pediatric enabled an early tension-less fascial closure in GOC and GS in the newborn period.